2022
DOI: 10.1038/s41433-022-02009-2
|View full text |Cite
|
Sign up to set email alerts
|

Post photorefractive keratectomy (PRK) infectious keratitis; six-year experience of a tertiary eye hospital

Abstract: BACKGROUND/OBJECTIVES: As an essential development in the new century, surface ablation procedures have attracted increasing attention. There exists a concern regarding the risk of infectious keratitis. Hence, we aimed to investigate the rate and predisposing factors of infectious keratitis after photorefractive keratectomy (PRK). SUBJECTS/METHODS: This retrospective study was designed in two phases. First, the rate of post-PRK keratitis of Farabi Eye Hospital was investigated. In other words, the targeted pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, this study found that prolonged use of BCLs did not increase the risk of infectious keratitis, as the corneal epithelium healed in most patients within 4 days after surgery, and patients were administered antibiotic eye drops before removing the BCLs. Additionally, infectious keratitis following TransPRK is usually associated with a favorable prognosis [ 33 ], and both cases of infectious keratitis in this study were successfully treated, and resulting in a final UDVA of at least 0.0 LogMAR.…”
Section: Discussionmentioning
confidence: 94%
“…However, this study found that prolonged use of BCLs did not increase the risk of infectious keratitis, as the corneal epithelium healed in most patients within 4 days after surgery, and patients were administered antibiotic eye drops before removing the BCLs. Additionally, infectious keratitis following TransPRK is usually associated with a favorable prognosis [ 33 ], and both cases of infectious keratitis in this study were successfully treated, and resulting in a final UDVA of at least 0.0 LogMAR.…”
Section: Discussionmentioning
confidence: 94%
“…Thirteen of these patients had a history of blepharitis, meibomitis, and dry eyes. 14 16 Diabetes mellitus was discovered in four cases (Table 1 ). 55 , 56 …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 84 studies meeting the inclusion criteria were included in this review, and 306 infectious eyes (involving 279 patients) after refractive surgery were analyzed. The mean age of patients was 36.9611.0 years (ranging from 16…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schallhorn et al [37] have conducted a review of suspected microbial keratitis cases after laser refractive surgery from 2008 to 2015, reporting an incidence of 0.013% for post-PRK and 0.0046% for post-LASIK microbial keratitis. Soleimani et al [38] have found an overall incidence of 0.02% for keratitis post-PRK. Liu et al [39] have retrospectively summarized the clinical treatments of patients who undergo SMILE in local hospital from 2019 to 2021, only 5 patients develops infectious corneal infiltration.…”
Section: Infectious Keratitis After Laser Vision Correctionmentioning
confidence: 98%